Molecular profile of a pleomorphic adenoma of the hard palate: A case report. Issue 29 (17th July 2020) - Iida, Yoshiyuki; Serizawa, Masakuni; Mukaigawa, Takashi; Kamijo, Tomoyuki; Nakajima, Takashi; Asakura, Koiku; Kusuhara, Masatoshi; Yamaguchi, Ken; Onitsuka, Tetsuro
Abstract: Rationale: Pleomorphic adenoma (PA) is the most common benign tumor of salivary glands. PAs have the potential for regional and distant metastases that preserve their benign phenotype; they also have the potential for malignant transformation. The molecular pathogenesis of malignant neoplasms has been studied extensively in recent years, unlike that of benign tumors, such as PA. Patient concerns: In this case report, we identified the molecular signatures of a 57-year-old Japanese woman. Our patient presented with a swelling of the hard palate with an erosive appearance. Diagnoses: The patient was diagnosed with a right hard palate tumor suspected to be a malignant neoplasm. Interventions: Partial maxillary resection and reconstruction were performed. Outcomes: There was no obstacle to swallowing or dysarthria after surgery. There was no sign of recurrent palatal tumor 4 years after the operation. Using next generation sequencing, 5 nonsynonymous mutations and CHCHD7-PLAG1 fusion genes were detected. Moreover, gene expression profiling indicated the possibility of the activation of several cancer-related signaling pathways. Although the PLAG1 gene is predicted to play a crucial role in PA tumorigenesis, its over-expression is reported to mediate multiple downstream factors. In this case, various up- and downregulated RNA signaling pathways, including MAP kinase signaling, PI3K/AKT1/MTOR signaling, JAK/STAT signaling, and PD-L1 signaling, were revealed. Lessons: These molecular profiles of PA may elucidate the mechanism of metastasis, preserving its benign phenotype and carcinoma ex PA.